The Influence of Enterprise Resource Planning, Liquidity, and Corporate Social Responsibility on Financial Performance - Arinda Tri Kusuma Dewi; Rr. Tjahjaning Poerwati (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to determine and examine the influence of Enterprise Resource Planning (ERP), Liquidity, and Corporate Social Responsibility (CSR) on Financial Performance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This research uses quantitative data in the form of annual reports and sustainability reports of manufacturing companies obtained from the official website of the Indonesia Stock Exchange (IDX) at www.idx.co.id and the related company websites. The data collection technique used the documentation method, with 23 companies meeting the criteria for this study. The data analysis technique used in this research employs quantitative analysis techniques, specifically Multiple Linear Regression. (Multiple Linear Regression). The statistical program used in this research is SPSS 26.0 to test the influence of independent variables on the dependent variable. The results of this study indicate that the variables Enterprise Resource Planning (ERP), Liquidity, and Corporate Social Responsibility (CSR) have a positive and significant impact on financial performance (ROA).